Problematika Kebijakan Pengelolaan Sampah di Kabupaten Banyumas - Pazqara, Emiraldo Win (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
Abstract Writing this scientific paper aims to describe the implementation of waste management policies in the Banyumas Regency area. The research uses a qualitative descriptive analysis model with competent informants in carrying out policies. The results of the analysis show that the implementation of waste management policies in Banyumas Regency from the communication aspect is quite good, it can be seen from the running of the policy socialization mechanism carried out by the office which is routine and quite intense to the community. Second, from the aspect of resources, it can be seen from implementing officials who understand the policy, but are constrained in efforts to change the mindset of the people who are used to being served in managing waste. Third, from the disposition aspect, it can be seen from the distribution of authority that is going well and coordinatively, including the implementation of the principle of partnership with the community through KSM, but on the other hand, it is constrained by the lack of experience of partners and limited operational funds. Fourth, from the aspect of bureaucratic structure, it can be seen from the availability of policy SOPs, including the functioning of the work monitoring and reporting system. Keywords: Public Policy, Waste Management, Local Government  AbstrakPenulisan karya ilmiah ini bertujuan untuk mendeskripsikan implementasi kebijakan pengelolaan sampah di wilayah Kabupaten Banyumas. Penelitian menggunakan model analisis deskriptif kualitatif dengan informan pihak-pihak yang berkompeten dalam menjalankan kebijakan. Hasil analisis menunjukkan bahwa implementasi kebijakan pengelolaan sampah di Kabupaten Banyumas dari aspek komunikasi berlangsung cukup baik, terlihat dari berjalannya mekanisme sosialisasi kebijakan yang dijalankan oleh dinas yang bersifat rutin serta cukup intens kepada masyarakat. Kedua, dari aspek sumber daya, terlihat dari aparat pelaksana yang memahami kebijakan, namun terkendala dalam upaya mengubah pola pikir masyarakat yang terbiasa dilayani dalam mengelola sampah. Ketiga, dari aspek disposisi, terlihat dari pembagian wewenang yang berjalan dengan baik dan koordinatif termasuk berjalannya prinsip kemitraan dengan masyarakat melalui KSM, namun di sisi lain terkendala dalam hal kurangnya pengalaman mitra kerja dan keterbatasan dana operasional. Keempat, dari aspek struktur birokrasi, terlihat dari ketersediaan SOP kebijakan, termasuk berjalannya sistem pengawasan dan pelaporan kerja.Kata Kunci: Kebijakan Publik, Manajemen Sampah, Pemerintah Daerah